Khyber Pakhtunkhwa health sector review hospital care. - Osti, Rabindra (Asian Development Bank, 2019)
Fast demographic growth, poor access to and utilization of health services, an underfunded public health system, and fragmented reform initiatives are among the key challenges in the province. The Government of Khyber Pakhtunkhwa commissioned the Asian Development Bank to conduct the review to aid the creation of a comprehensive strategy to guide investments and projects in the health sector.